2007
DOI: 10.1074/jbc.m705133200
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase-3α Reduces Cardiac Growth and Pressure Overload-induced Cardiac Hypertrophy by Inhibition of Extracellular Signal-regulated Kinases

Abstract: Glycogen synthase kinase-3 (GSK-3) is a serine/threonine kinase having multiple functions and consisting of two isoforms, GSK-3␣ and GSK-3␤. Pressure overload increases expression of GSK-3␣ but not GSK-3␤. Despite our wealth of knowledge about GSK-3␤, the function of GSK-3␣ in the heart is not well understood. To address this issue, we made cardiac-specific GSK-3␣ transgenic mice (Tg). Left ventricular weight and cardiac myocyte size were significantly smaller in Tg than in non-Tg (NTg) mice, indicating that G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 40 publications
6
68
2
2
Order By: Relevance
“…Prior studies examining effects of GSK-3s on TAC-induced LV dysfunction have suggested that increased activity of GSK-3α, by either transgenesis or knockin, led to declines in LV function, suggesting GSK-3α signaling is detrimental (13,14). In distinct contrast, our lossof-function studies identify a clear and critical role for GSK-3α in preserving LV function in the setting of pressure stress.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…Prior studies examining effects of GSK-3s on TAC-induced LV dysfunction have suggested that increased activity of GSK-3α, by either transgenesis or knockin, led to declines in LV function, suggesting GSK-3α signaling is detrimental (13,14). In distinct contrast, our lossof-function studies identify a clear and critical role for GSK-3α in preserving LV function in the setting of pressure stress.…”
Section: Discussioncontrasting
confidence: 50%
“…Findings with GSK-3α have been even less clear. Whereas a constitutively active transgenic repressed the hypertrophic response to TAC, the same mutant expressed in a knockin model showed an increased hypertrophic response (13,14). These disparate and confusing findings, which led Sugden et al to state "we just do not know whether to inhibit or activate GSK-3, or simply not to interfere" (29), highlight the need to examine loss-of-function approaches that do not rely on transgenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations